If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(x-1)=-3x-2
We simplify the equation to the form, which is simple to understand
-3(x-1)=-3x-2
Reorder the terms in parentheses
+(-3x+3)=-3x-2
Remove unnecessary parentheses
-3x+3=-3x-2
We move all terms containing x to the left and all other terms to the right.
-3x+3x=-2-3
We simplify left and right side of the equation.
0x=-5
0=-5
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| -0.25x-2=-6 | | 6xy+3xy+6xy+10xy=989 | | 5x^2-34=x | | -0.5x+5=0 | | 5a-a-2a= | | 6xy+3xy+6xy+10xy= | | 3[5+2(9-8)]= | | 12x-2=24x+2 | | 2x*2+2x*x+1x+2= | | 0.25x+10x-2=121 | | 4x+32=8x | | 5+.75x=-7 | | x^3+x^2+2x-3=0 | | 0.5x-5x+8=-28 | | 2-3+8= | | 7y+13=13y+7 | | -7-15=8 | | 2x+60=2x^2 | | 4n=6*1 | | (x/4)+6=13 | | 6d-3d+2d= | | 2ax+1=ax+5 | | 2x+4x-7=17 | | 8x-5=0 | | 5n+6=4 | | Xt-5=k | | 9+5=5a+5 | | 19x-41=41 | | 7x+18y=4 | | 19x-41=-41 | | 7y-9=8y-1 | | -2(r+6)=-37 |